FUNGSI DAN KEDUDUKAN SAKSI YANG MERINGANKAN (A DE CHARGE) SEBAGAI ALAT BUKTI DALAM SIDANG PERKARA PIDANA - Harianto, Tomi; Wibowo, Adhi (UNES Journal of Swara Justisia, 2017)
Given the importance of the presence of a witness in the criminal justice process to discover material truths, the function and position of witnesses are privileged and desirable for the parties involved in the criminal justice process. Especially for the relieving witness, his presence is expected by the defendant to provide information in the proceedings aimed at relieving the defendant and can be used as a consideration for the prosecutor in filing a lawsuit in the criminal justice process, as well as to convince the judge in taking the decision. Witnesses filed by a suspect or a defendant who is expected to provide a favorable testimony to him is called a de charge witness.